How Different Methodologies of Harvesting and Analysing the Samples Affect the Test Results in Determining Joint Mediators. (20th February 2013) - Yilmaz, Ibrahim; Gokay, Nevzat Selim; Bircan, Rifat; Saracoglu, Gamze V.; Dervisoglu, Sergulen; Gokce, Alper
Abstract : Purpose . This study has researched the affect of different methodologies of harvesting and analysing the samples in determining the mediators emerging after the rat articular cartilage injury. Materials and Methods . One hundred and forty-four male wistar rats were divided into 2 groups. Synovial fluid samples were taken from all of the rats. We entered into the right knees of the rats in group I ( n = 36 ) under anaesthesia and took cartilage tissue samples from their distal femur. Samples were taken as reference values for enzyme linked immunosorbent assay (ELISA) and histopathological evaluations. We entered into the right knees of the rats in group II ( n = 108 ) and formed complete layer of cartilage injury in their medial femoral condyles. At the end of the 15th day, the rats were sacrificed after taking synovial fluid samples from their right knees creating defect in the rats in group II. The molecular markers in the synovial fluid and cartilage tissue samples which were taken from the experimental and control groups (MMP-9, MMP-13, TIMP-1, TNF- α, and NO) were analysed by direct or indirect methodologies. SPSS 18.0 Package program was used in the statistical evaluation. Students t- test where the measurement variables between the experimental and control groups were compared was applied. Receiver Operating Characteristics (ROC) curves were used in the determination of the diagnostic sufficiency from the tissue. Results . No difference was found between TIMP-1 ( P = 0.67 ) and MMP-9 ( P = 0.28 ) levels in synovial fluid and cartilage tissue. From the molecular markers, when MMP-9, MMP-13, NO, TIMP-1, TNF- α ′, the area under ROC curve, and P values were examined, MMP-13 (P < 0.0001, 95% CI: 0.70–0.85), NO (P < 0.0001, 95% CI: 0.72–0.86), and TNF- α (P < 0.0001, 95% CI: 0.91–0.98) results were found to be statistically significant. Inferences . The indirect ELISA protocol which we apply for the cartilage tissue as an alternative to synovial lavage fluid is a reliable method which can be used in the determination of articular cartilage injury markers.